Role of HIF-1α/ERRα in Enhancing Cancer Cell Metabolism and Promoting Resistance of Endometrial Cancer Cells to Pyroptosis - Su, Pingping; Yu, Lirui; Mao, Xiaodan; Sun, Pengming (Frontiers in Oncology, 2022)
Oxygen is critical to energy metabolism, and tumors are often characterized by a hypoxic microenvironment. Owing to the high metabolic energy demand of malignant tumor cells, their survival is promoted by metabolic reprogramming in the hypoxic microenvironment, which can confer tumor cell resistance to pyroptosis. Pyroptosis resistance can inhibit anti-tumor immunity and promote the development of malignant tumors. Hypoxia inducible factor-1α (HIF-1α) is a key regulator of metabolic reprogramming in tumor cells, and estrogen-related receptor α (ERRα) plays a key role in regulating cellular energy metabolism. Therefore, the close interaction between HIF-1α and ERRα influences the metabolic and functional changes in cancer cells. In this review, we summarize the reprogramming of tumor metabolism involving HIF-1α/ERRα. We review our understanding of the role of HIF-1α/ERRα in promoting tumor growth adaptation and pyroptosis resistance, emphasize its key role in energy homeostasis, and explore the regulation of HIF-1α/ERRα in preventing and/or treating endometrial carcinoma patients. This review provides a new perspective for the study of the molecular mechanisms of metabolic changes in tumor progression.